ECONOMY OF HIGHER EDUCATION: SPACE OF RISKS AND THREATS - Valeriy V. Gamukin (Moscow Polytechnic University, 2016)
The article analyzes the current state of economy sector of higher education in Russia. It is noted that the efficiency of education depends on the efficiency of its institutions. The author draws a conclusion on the exhaustion of opportunities of the working model of professional education financing. Two new models of financing, capable to have an impact onthe increase of the efficiency of institutions of education are offered. The first model assumesan increase in cost of training on condition of increase in the period of calculation. The second model assumes strengthening of a role of state regulation of the financial relations in higher education at reduction of volumes of the budgetary financing. Features of models in relation to an open foreign market of educational services are specified. Problems of growth of the efficiency at preservation of modern budgetary financing are noted.